(untitled) (Modern education and development, 2025)
Bilingualism, the fluent use of two languages, offers cognitive and social benefits but also raises concerns about linguistic hegemony. This paper examines how bilingualism facilitates communication while potentially marginalizing minority languages. It explores the impact of language policies, media, and education on linguistic diversity, emphasizing the need for sustainable multilingual strategies.